DEVELOPMENT OF CREATIVITY OF THE FUTURE SPECIALIST IN BY CONVERSION EDUCATIONAL MATERIAL - L.L. Oleksiyenko (Academy of Cognitive and Natural Sciences, 2008)
At this article is considered mechanisms of self-development creativity of future specialists as natural basic of their creative using of the professional functions in own activity with the help of changing educational information in educational process.